2020
DOI: 10.1016/j.bbmt.2019.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Simple Approach to Increase Donor Hematopoietic Stem Cell Dose and Improve Engraftment in the Murine Model of Allogeneic In Utero Hematopoietic Cell Transplantation

Abstract: The rationale for in utero hematopoietic cell transplantation (IUHCT) rests on exploitation of normal events during hematopoietic and immunologic ontogeny to allow allogeneic hematopoietic engraftment without myeloablative conditioning. Host hematopoietic competition is among the primary barriers to engraftment in IUHCT. In the murine model this can be partially overcome by delivery of larger donor cell doses, but volume is limiting. Enrichment of donor hematopoietic stem cells (HSCs) would seem to offer a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies from sheep model showed that engraftment after IUHCT was dose-dependent, which seemed to reach a plateau above the optimal dose (Zanjani et al, 1997). Moreover, Vrecenak et al (2020) demonstrated that increasing doses of Lin-cells combined with BM could dramatically improve both allogeneic early and late engraftment after IUHCT.…”
Section: Increasing Donor Cell Dosage or Repopulating Competencymentioning
confidence: 97%
“…Studies from sheep model showed that engraftment after IUHCT was dose-dependent, which seemed to reach a plateau above the optimal dose (Zanjani et al, 1997). Moreover, Vrecenak et al (2020) demonstrated that increasing doses of Lin-cells combined with BM could dramatically improve both allogeneic early and late engraftment after IUHCT.…”
Section: Increasing Donor Cell Dosage or Repopulating Competencymentioning
confidence: 97%
“…Some potential strategies proposed have included RNA interferences, antibodies that target the fetal hematopoietic progenitors, targeted delivery of proapoptotic peptides to host stem cells, treatment of gene therapies with growth factors, 98 and adding enriched bone marrow to treatments. 99 PIDs have been at the forefront of many cutting-edge treatments, such as HSCT and postnatal gene therapies. While there are many barriers to overcome for prenatal gene therapy to be a safe and effective option for patients, it is very likely that one of the PIDs will be one of the first diseases cured by this technology.…”
Section: In Utero Gene Therapymentioning
confidence: 99%
“…Therefore, other strategies to improve engraftment are needed. Some potential strategies proposed have included RNA interferences, antibodies that target the fetal hematopoietic progenitors, targeted delivery of proapoptotic peptides to host stem cells, treatment of gene therapies with growth factors,98 and adding enriched bone marrow to treatments 99…”
Section: In Utero Gene Therapymentioning
confidence: 99%